The resurgence of military coups and implications for democratic stability in sub-Saharan Africa - Mendy, Ousu; Mendy, Andrew (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2024)
Since the late 1980s, with no choice, there has been a strong wave of democracy and democratization in the continent with most of African countries beginning to move away from one-party or military dictatorships to multiparty democratic rule. There have been coup d'états on the African continent since the 1960s. However, the aim of this research is to examine the recent resurgence and growth of coups which is contrary to the consolidation and stability of democracy in Africa. It seeks to present the main trajectory of military coup d' etats in sub-Saharan Africa focusing on its implication to democratic stability in the region. To achieve this, researchers engage a qualitative research method with in-depth assessment of coups and their impact on the growth in sub-Saharan Africa. The results of this research show that recent military takeovers have brought attention to a troubling trend in African politics: a rise in the use of unconstitutional methods to change governments. Military coups are to certain extent direct responses to citizens' complaints considering bad governance, deteriorating citizens' living conditions, and rising levels of insecurity. This research, therefore, concludes that military coups expose sub-Saharan African to human rights violations. Due to these unpleasant conditions of sub-Saharan polity, men in uniform align to the view that it is through coups that they can oust out this civilian governments that have mutilated constitutions to allow them to rule their countries without term limit.